2009
DOI: 10.1136/bmj.b1555
|View full text |Cite
|
Sign up to set email alerts
|

Doctors as leaders

Abstract: Next week, the BMJ and The King’s Fund will hold a debate asking if doctors have neglected their duty to lead the NHS. Candace Imison and Richard W Giordano describe the importance of doctors as leaders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…[ 21 ] Many others have also suggested that placing physicians into leadership positions can result in improved hospital performance and patient care. [ 8 9 12 13 15 25 26 27 38 39 ] We believe that the conflicting measures of hospital quality and ranking systems can explain this difference.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Many others have also suggested that placing physicians into leadership positions can result in improved hospital performance and patient care. [ 8 9 12 13 15 25 26 27 38 39 ] We believe that the conflicting measures of hospital quality and ranking systems can explain this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that physician executives are more likely to use evidence-based decision making with an increasing emphasis on quality metrics and patient outcomes (Imison and Giordano, 2009;Falcone and Satiani, 2008), thereby driving higher patient satisfaction (Galstian et al, 2018) and hospital ratings. Large physician-led hospital systems, for example, received higher ratings and bed usage rates than did hospitals led by nonphysicians, with no differences in financial performance (Tasi et al, 2019).…”
Section: Physician Ceo and Hospital Performancementioning
confidence: 99%
“…, 2016). Physician-led hospitals experienced improved patient outcomes (Imison and Giordano, 2009; Falcone and Satiani, 2008), enjoyed higher financial performance and had 25% overall quality scores higher than those run by non-physicians (Gupta, 2019). Other studies found positive relationship between participation of physicians on boards and improved hospital performance including higher quality ratings and lower morbidity rates (Bai and Krishnan, 2015; Veronesi et al ., 2013), better performance by hospital management staff and more effective utilization of clinical quality metrics on target settings and operations (Tsai et al.…”
Section: Introductionmentioning
confidence: 99%
“…In unison with international discontent, clinicians protested that their capacity to lead had been undermined by managers, to the detriment of their patients. 7 The scene was set with a lack of expert leadership, combined with a detached centralised managerial structure that was trying to operationalize a policy, which seemed to be translating into a fundamental drive to close acute psychiatric beds. This saw an extraordinary decision that led to a crisis in eating disorder care in SA.…”
Section: Outcomes Of a Manager-led Servicementioning
confidence: 99%
“…In unison with international discontent, clinicians protested that their capacity to lead had been undermined by managers, to the detriment of their patients. 7…”
Section: Outcomes Of a Manager-led Servicementioning
confidence: 99%